The Relationship Between Verbal And Non-Verbal Communication Of Nurses To Level Of Patient Satisfaction At Mattombong Health Center Pinrang District - Andang, Baharuddin; Al Adawiah, St. Arabiah Tul' (Jurnal EduHealth, 2023)
Any interaction that involves nurses directly or indirectly is considered verbal communication, in contrast to non-verbal communication which is done gradually through attitude, body language, and tone of voice because the problem that usually leads to customer dissatisfaction is the lack of communication between officers and clients, customers will be happy if the health services they receive meet or exceed their expectations. Effective communication requires good interpersonal communication skills from nurses. The purpose of this study was to determine the relationship between verbal and non-verbal communication of nurses with the level of satisfaction at Mattombong Health Center, Pinrang Regency. Data were collected using a questionnaire sheet and then analyzed by cross sectional quantitative analysis method, the population in the study amounted to 43 patients, the research sample was 33 patients who had been carried out on June 15 to July 15, 2023. The results showed that there was a relationship between verbal communication and the level of patient satisfaction with the results of p=0.004 <0.05 and there was a relationship between non-verbal communication and patient satisfaction as evidenced by the value of p=0.002 <0.05.